Sosialisasi Hukum Pidana Sebagai Upaya Pemberdayaan Masyarakat Menuju Lingkungan Yang Tertib Hukum (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2026)
Criminal law socialization is a crucial form of community empowerment in building awareness, compliance, and legal order in the social environment. This activity is motivated by the limited understanding among some members of the public regarding what constitutes a crime, the potential legal consequences, and the appropriate steps to take when facing legal issues. This lack of legal literacy can leave people vulnerable to committing violations, becoming victims of crime, or resolving conflicts in ways that are inconsistent with legal provisions. Therefore, this socialization activity aims to provide a basic understanding of criminal law, raise public awareness of the importance of obeying the law, and encourage active community participation in creating a safe, orderly, and just environment. The activity is implemented through counseling, interactive discussions, questions and answers, and the presentation of simple case studies relevant to everyday life. The material presented includes the definition of criminal law, types of crimes frequently occurring in society, legal sanctions, the rights and obligations of citizens, and the role of the community in preventing legal violations. Through a communicative and participatory approach, it is hoped that the community will more easily understand the material and be able to connect it to real-world problems in their environment. The expected outcomes of this activity are increased public understanding of criminal law, increased awareness to avoid unlawful acts, and increased public courage to report criminal acts to the authorities. Thus, criminal law socialization serves not only as an educational activity but also as a community empowerment strategy in building a legal culture. This activity is expected to encourage the formation of a legally aware, responsible community that plays an active role in creating a law-abiding environment.